Clinically Focused Molecular Investigation of 1000 Consecutive Families with Inherited Retinal Disease - Stone, Edwin M.; Andorf, Jeaneen L.; Whitmore, S. Scott; DeLuca, Adam P.; Giacalone, Joseph C.; Streb, Luan M.; Braun, Terry A.; Mullins, Robert F.; Scheetz, Todd E.; Sheffield, Val C.; Tucker, Budd A. (Ophthalmology (Rochester, Minn.), 2017)
To devise a comprehensive multiplatform genetic testing strategy for inherited retinal disease and to describe its performance in 1000 consecutive families seen by a single clinician. Retrospective series. One thousand consecutive families seen by a single clinician. The clinical records of all patients seen by a single retina specialist between January 2010 and June 2016 were reviewed, and all patients who met the clinical criteria for a diagnosis of inherited retinal disease were included in the study. Each patient was assigned to 1 of 62 diagnostic categories, and this clinical diagnosis was used to define the scope and order of the molecular investigations that were performed. The number of nucleotides evaluated in a given subject ranged from 2 to nearly 900 000. Sensitivity and false genotype rate. Disease-causing genotypes were identified in 760 families (76%). These genotypes were distributed across 104 different genes. More than 75% of these 104 genes have coding sequences small enough to be packaged efficiently into an adeno-associated virus. Mutations in ABCA4 were the most common cause of disease in this cohort (173 families), whereas mutations in 80 genes caused disease in 5 or fewer families (i.e., 0.5% or less). Disease-causing genotypes were identified in 576 of the families without next-generation sequencing (NGS). This included 23 families with mutations in the repetitive region of RPGR exon 15 that would have been missed by NGS. Whole-exome sequencing of the remaining 424 families revealed mutations in an additional 182 families, and whole-genome sequencing of 4 of the remaining 242 families revealed 2 additional genotypes that were invisible by the other methods. Performing the testing in a clinically focused tiered fashion would be 6.1% more sensitive and 17.7% less expensive and would have a significantly lower average false genotype rate than using whole-exome sequencing to assess more than 300 genes in all patients (7.1% vs. 128%; P < 0.001). Genetic testing for inherited retinal disease is now more than 75% sensitive. A clinically directed tiered testing strategy can increase sensitivity and improve statistical significance without increasing cost.